The Chief Financial Officer's Perspective on Auditor‐Client Negotiations* - Gibbins, Michael; McCracken, Susan A.; Salterio, Steve E. (Contemporary Accounting Research, 2007)
Auditor-client negotiation about difficult client accounting issues involves both the auditor and the client. On the client side, the Chief Financial Officer (CFO) plays a central role in the financial reporting process, yet is rarely the focus of academic study. This paper reports how a sample of Canadian CFOs viewed the negotiation process and context, using an experiential questionnaire to build on the negotiation model developed and demonstrated for the auditor side of the negotiation by Gibbins, Salterio, and Webb 2001, and corroborated by a comparison of common questionnaire items across auditor and CFO samples by Gibbins, McCracken, and Salterio 2005. The CFOs saw negotiation with the auditors as a consequence of change in accounting and disclosure standards or personnel influential to their financial reporting, or business changes, such as, new business deals or acquisitions. Negotiation was thrust upon the CFO, and the CFO then had to manage it. The CFOs informed other management (such as the CEO) and was aware of their interests, but did not generally seek their help. Informing the Board or the audit committee of the issue was much less frequent. The issue being negotiated was seen as complex, requiring research and analysis, and dependent on knowledge and expertise, with the result more likely reflecting form over substance (a result some CFOs suggested was more agreeable to the auditor than to the CFO).